Release film for ceramic green sheet manufacturing process

JP7645109B2Active Publication Date: 2025-03-13LINTEC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021045164
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-18
Publication Date
2025-03-13
Estimated Expiration
2041-03-18

AI Technical Summary

Benefits of technology

【0017】 本発明に係るセラミックグリーンシート製造工程用剥離フィルムは、当該剥離フィルム上でセラミックグリーンシートを裁断する際に、裁断部に浮きが発生し易い。当該浮きは、セラミックグリーンシートを剥離する際のきっかけとして有効に利用できる。そのため、本発明に係るセラミックグリーンシート製造工程用剥離フィルムは、セラミックグリーンシートを剥離し易いものである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645109000002
    Figure 0007645109000002
  • Figure 0007645109000003
    Figure 0007645109000003
  • Figure 0007645109000004
    Figure 0007645109000004
Patent Text Reader

Abstract

To provide a release film for a ceramic green sheet manufacturing process, which allows a ceramic green sheet to be easily released.SOLUTION: There is provided a release film 1 for a ceramic green sheet manufacturing process, the film including a substrate 11 and a release agent layer 12 provided on one side of the substrate 11. An elastic deformation work rate is 45% or more, an elastic displacement amount is 1.90 μm or less, and a plastic displacement amount is 1.12 μm or less in a load displacement curve measured when a load of 20 mN is applied to the release agent layer 12 side of the release film 1 for a ceramic green sheet manufacturing process, using a microsurface hardness tester.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a release film used in the process of producing a ceramic green sheet. [Background technology]

[0002] Conventionally, multilayer ceramic products such as multilayer ceramic capacitors and multilayer ceramic substrates have been produced by forming ceramic green sheets, stacking a plurality of the resulting ceramic green sheets, and firing the stacked sheets.

[0003] The ceramic green sheet is formed by coating a ceramic slurry containing a ceramic material such as barium titanate or titanium oxide on a release film. The release film is required to have releasability that allows the release film to be peeled off from the thin ceramic green sheet formed on the release film with an appropriate peeling force without cracking, breaking, or the like.

[0004] As the release film, one in which a film-like substrate is subjected to release treatment with a release agent to form a release agent layer is usually used (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2020-49803 [Patent Document 2] Patent No. 6610810 Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, there has been a demand for more precise and smaller laminated ceramic products, and the ceramic green sheets being molded are becoming thinner. The thinner the sheets are, the more difficult it becomes to peel the ceramic green sheets from the release film. Therefore, there is a demand for a release film that makes it easier to peel the ceramic green sheets.

[0007] The inventors have noticed that when a molded ceramic green sheet is cut on a release film, the edge of the ceramic green sheet (hereinafter, sometimes referred to as a "cut portion") generated when the ceramic green sheet is divided by a cutting blade is in a state of floating from the release film. In particular, the inventors have found that such "floating" can be effectively used as a starting point for peeling off the ceramic green sheet.

[0008] The present invention has been made in view of the above circumstances, and has an object to provide a release film for use in the ceramic green sheet production process, which allows easy peeling of the ceramic green sheet. [Means for solving the problem]

[0009] In order to achieve the above-mentioned object, first, the present invention provides a release film for use in a ceramic green sheet production process, comprising a substrate and a release agent layer provided on one side of the substrate, characterized in that, in a load-displacement curve measured when a load of 20 mN is applied to the release agent layer side of the release film for use in the ceramic green sheet production process using a micro-surface hardness tester, the elastic deformation power is 45% or more, the elastic displacement amount is 1.90 μm or less, and the plastic displacement amount is 1.12 μm or less (Invention 1).

[0010] In the above invention (Invention 1), the base material preferably contains a filler (Invention 2).

[0011] In the above invention (Invention 2), the filler is preferably a hydroxyapatite-based filler (Invention 3).

[0012] In the above inventions (Inventions 2 and 3), it is preferable that the substrate comprises at least a first resin layer containing the filler, and a second resin layer laminated on one side of the first resin layer and not containing the filler (Invention 4).

[0013] In the above inventions (Inventions 1 to 4), the arithmetic mean roughness (Ra) of the release agent layer on the surface opposite to the substrate is preferably 1 nm or more and 20 nm or less (Invention 5).

[0014] In the above inventions (Inventions 1 to 5), the maximum projection height (Rp) of the release agent layer on the surface opposite to the substrate is preferably 10 nm or more and 200 nm or less (Invention 6).

[0015] In the above inventions (Inventions 1 to 6), the thickness of the release agent layer is preferably 10 nm or more and 1000 nm or less (Invention 7).

[0016] In the above inventions (Inventions 1 to 7), the thickness of the substrate is preferably 10 μm or more and 100 μm or less (Invention 8). Effect of the Invention

[0017] The release film for use in the ceramic green sheet manufacturing process according to the present invention is prone to causing lifting at the cut portion when a ceramic green sheet is cut on the release film. The lifting can be effectively utilized as a trigger for peeling off the ceramic green sheet. Therefore, the release film for use in the ceramic green sheet manufacturing process according to the present invention makes it easy to peel off the ceramic green sheet. [Brief description of the drawings]

[0018] [Figure 1] FIG. 2 is a cross-sectional view of a release film for use in a ceramic green sheet manufacturing process according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a schematic view of a ceramic green sheet being cut on a release film for a ceramic green sheet manufacturing process according to one embodiment of the present invention. [Diagram 3] FIG. 2 is an enlarged cross-sectional view showing a schematic view of a ceramic green sheet being cut on a release film for a ceramic green sheet manufacturing process according to one embodiment of the present invention. [Figure 4] FIG. 1 is an enlarged cross-sectional view that illustrates a schematic view of a ceramic green sheet being cut on a release film for use in a conventional ceramic green sheet manufacturing process. [Diagram 5] FIG. 2 is a schematic diagram showing a load-displacement curve. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described. 1 is a cross-sectional view of an example of a release film for use in the ceramic green sheet manufacturing process according to this embodiment. As shown in the figure, a release film for use in the ceramic green sheet manufacturing process according to this embodiment (hereinafter, may be simply referred to as a "release film") 1 includes a substrate 11 and a release agent layer 12 provided on one side of the substrate 11. The release film 1 according to this embodiment may further include an intermediate layer between the substrate 11 and the release agent layer 12.

[0020] In the release film 1 of this embodiment, in the load-displacement curve measured when a load of 20 mN is applied to the release agent layer 12 side of the release film 1 using a micro-surface hardness tester, the elastic deformation power is 45% or more, the elastic displacement is 1.90 μm or less, and the plastic displacement is 1.12 μm or less.

[0021] The release film 1 according to the present embodiment, which satisfies these physical properties, can effectively generate a lift at the cut portion of the ceramic green sheet when the molded ceramic green sheet is cut on the release film 1. FIG. 2 shows a schematic diagram of such cutting. As shown in the figure, cutting is performed using a cutting blade 4 in a state where a laminate of the molded ceramic green sheet 2 and the release film 1 is placed on a support table 3. At this time, the cutting blade 4 is inserted from the surface on the ceramic green sheet 2 side and pressed down until a part of the release film 1 is cut. This causes the ceramic green sheet 2 to be completely cut. When the release film 1 according to the present embodiment is used, a "lift 5" is easily generated in which the end of the ceramic green sheet 2 is locally separated from the release film 1 at the position (cut portion) where the cutting blade 4 has entered. This lift 5 can be effectively used as a starting point when separating the ceramic green sheet 2 from the release film 1 after cutting. That is, only the release film 1 can be easily gripped at the position of the float 5, and the ceramic green sheet 2 and the release film 1 can be satisfactorily separated without applying an unnecessary load to the ceramic green sheet 2.

[0022] As described above, the reasons why the release film 1 according to the present embodiment is prone to the lifting 5 are considered to be as follows. However, the reasons are not limited to the following, and the possibility of a combination of other phenomena and other reasons or the existence of a completely different reason is not denied.

[0023] FIG. 3 is a schematic diagram showing how the ceramic green sheet 2 is cut by the release film 1 according to this embodiment. In particular, FIG. 3 is an enlarged view of the portion to be cut. In the release film 1 according to this embodiment, by satisfying the above-mentioned physical properties, when the cutting blade 4 is pressed in as shown in FIG. 3(a), the ceramic green sheet 2 is difficult to follow the release film 1. As a result, the edge generated by the cutting of the ceramic green sheet 2 is well separated from the release film 1, and the lift 5 is generated. Furthermore, as shown in FIG. 3(b), when the cutting blade 4 is pulled back, the release film 1 according to this embodiment is restored with force, and the distance between the edge of the ceramic green sheet 2 and the release film 1 (the distance indicated by "h" in the figure; hereinafter, sometimes referred to as the "height" of the lift 5) becomes larger. As a result, in the release film 1 according to this embodiment, a large lift 5 is generated, and the ceramic green sheet 2 can be well peeled off.

[0024] On the other hand, FIG. 4 shows a schematic diagram of a conventional release film 1' when cutting a ceramic green sheet 2. In particular, FIG. 4 shows an enlarged view of the portion to be cut. In the conventional release film 1', when the cutting blade 4 is pressed in as shown in FIG. 4(a), the ceramic green sheet 2 follows the release film 1. As a result, the edge of the ceramic green sheet 2 generated by cutting remains almost in close contact with the release film 1, and good lifting 5 does not occur. Furthermore, as shown in FIG. 4(b), when the cutting blade 4 is pulled back, the restoration of the conventional release film 1' is insufficient, and the distance between the edge of the ceramic green sheet 2 and the release film 1' (the distance indicated by "h'" in the figure) is not sufficiently large. As a result, it is difficult to peel off the ceramic green sheet 2 with the conventional release film 1'.

[0025] In the release film 1 according to this embodiment, the elastic deformation power in the load-displacement curve measured when a load of 20 mN is applied to the release agent layer 12 in the release film 1 using a micro surface hardness tester (hereinafter, sometimes simply referred to as "elastic deformation power") is 45% or more, more preferably 48% or more, and even more preferably 50% or more. When the lower limit of the elastic deformation power is within the above range, the release film 1 is easily restored even if it is deformed by the force applied when cutting the ceramic green sheet. As a result, when the ceramic green sheet 2 is cut, a lift 5 is easily generated in the ceramic green sheet 2 at the cut portion, resulting in better releasability.

[0026] Moreover, the release film 1 according to this embodiment preferably has an elastic deformation power of 55% or less, more preferably 53% or less, and even more preferably 52% or less. When the upper limit of the elastic deformation power is within the above range, it becomes easy to suppress wear of the cutting blade 4. The method of calculating the elastic deformation power is as shown in the test example described later.

[0027] In the release film 1 according to this embodiment, the elastic displacement amount (hereinafter sometimes simply referred to as "elastic displacement amount") in the load-displacement curve measured when a load of 20 mN is applied to the release agent layer 12 in the release film 1 using a micro surface hardness tester is 1.90 μm or less. By setting the upper limit of the elastic displacement amount within the above range, the brittleness of the release film 1 is suppressed, and the tensile strength of the release film cut into by cutting is maintained, resulting in good processability of the ceramic green sheet 2.

[0028] Moreover, the release film 1 according to this embodiment preferably has an elastic displacement of 1.50 μm or more, more preferably 1.70 μm or more, and even more preferably 1.80 μm or more. When the lower limit of the elastic displacement is within the above range, the recovery distance of the release film 1 immediately after cutting becomes sufficient, and the height of the floating 5 of the ceramic green sheet also tends to become large.

[0029] In the release film 1 according to this embodiment, the plastic displacement in the load-displacement curve measured when a load of 20 mN is applied to the release agent layer 12 in the release film 1 using a micro surface hardness tester (hereinafter, sometimes simply referred to as "plastic displacement") is 1.12 μm or less, preferably 1.10 μm or less, and more preferably 1.08 μm or less. When the upper limit of the plastic displacement is within the above range, the edge of the ceramic green sheet 2 is less likely to follow the cutting blade 4 and be pressed into the release film 1. This makes it easier for a lift 5 to occur in the cut portion of the ceramic green sheet 2 when the ceramic green sheet is cut, resulting in better releasability.

[0030] Moreover, the release film 1 according to the present embodiment preferably has a plastic deformation of 1.00 μm or more, more preferably 1.02 μm or more, and even more preferably 1.04 μm or more. When the lower limit of the plastic deformation is within the above range, the height of the lift 5 can be made larger.

[0031] 1. Properties of release films used in the ceramic green sheet manufacturing process In the release film 1 according to this embodiment, the arithmetic mean roughness (Ra) of the surface of the release agent layer 12 opposite to the substrate 11 is preferably 20 nm or less, more preferably 15 nm or less, and even more preferably 10 nm or less. As ceramic green sheets become thinner, the surface of the release agent layer 12 of the release film 1 is required to have higher smoothness. When the upper limit of the arithmetic mean roughness is within the above range, a uniform ceramic green sheet can be formed. In addition, the lower limit of the arithmetic mean roughness (Ra) is not particularly limited, but is preferably 1 nm or more, more preferably 1.5 nm or more, and even more preferably 2 nm or more. The method for measuring the arithmetic mean roughness (Ra) is as shown in the test example described later.

[0032] In the release film 1 according to this embodiment, the maximum projection height (Rp) on the surface of the release agent layer 12 opposite to the substrate 11 is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less. A highly laminated and highly integrated multilayer ceramic capacitor (MLCC) requires a ceramic green sheet having a thickness of 1.0 μm or less. By setting the upper limit of the maximum projection height within the above range, even if the ceramic green sheet is a thin film, it becomes easy to suppress the occurrence of pinholes during production. In addition, the lower limit of the maximum projection height (Rp) is not particularly limited, but is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 30 nm or more. The method for measuring the maximum projection height (Rp) is as shown in the test example described later.

[0033] The peeling force required to peel the release film 1 from the ceramic green sheet formed on the release surface of the release film 1 according to this embodiment can be set appropriately, but is preferably 100 mN / 40 mm or less, particularly preferably 50 mN / 40 mm or less, and more preferably 30 mN / 40 mm or less. By setting the upper limit of the peeling force within the above range, better releasability can be exhibited. In addition, the lower limit of the peeling force is preferably a peeling force that does not cause unintended peeling from the formed ceramic green sheet, for example, preferably 5 mN / 40 mm or more, particularly preferably 10 mN / 40 mm or more. The method for measuring the peeling force is as shown in the test example described later.

[0034] The height of the floating 5 of the ceramic green sheet at the cut portion (height indicated by "h" in FIG. 3(b)) is preferably 1.0 μm or more, more preferably 1.5 μm or more, and even more preferably 2.0 μm or more. The height of the floating 5 is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 5 μm or less.

[0035] 2. Base material The substrate 11 of the release film 1 according to this embodiment is not particularly limited as long as it satisfies the above-mentioned conditions regarding the load-displacement curve when the release film 1 is constructed and the release agent layer 12 can be laminated thereon. Examples of materials for the substrate 11 include polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefin-based resins such as polyethylene, polypropylene, polybutene, polybutadiene, polymethylpentene, ethylene-norbornene copolymer, and norbornene resin; propylene-based copolymers such as ethylene-polypropylene random copolymer; ethylene-based copolymers such as ethylene-(meth)acrylic acid copolymer, ethylene-methyl(meth)acrylate copolymer, and other ethylene-(meth)acrylic acid ester copolymers; ethylene-vinyl acetate copolymer; polyvinyl chloride-based resins such as polyvinyl chloride copolymers; (meth)acrylic acid ester copolymers; polyurethane; polyimide; polystyrene; polycarbonate; and fluororesin. In addition, materials obtained by crosslinking these or ionomers thereof may be used. In this specification, "(meth)acrylic acid" refers to both acrylic acid and methacrylic acid. The same applies to other similar terms. Among the above-mentioned materials, it is preferable to use a polyester resin, in particular, it is preferable to use polyethylene terephthalate, and it is further preferable to use biaxially oriented polyethylene terephthalate, from the viewpoint of easily satisfying the above-mentioned conditions regarding the load-displacement curve.

[0036] The substrate 11 may be a film made of one of the above-mentioned materials, or may be a film made of multiple of the above-mentioned materials. Furthermore, the substrate 11 may be a laminated film made by laminating multiple such films. In this laminated film, the materials constituting each layer may be the same or different.

[0037] Moreover, from the viewpoint of easily satisfying the conditions related to the load-displacement curve described above, the substrate 11 preferably contains a filler, and in particular, it is preferable that the substrate 11 is a substrate in which a filler is added to the above-mentioned resin. The filler is not particularly limited as long as it can achieve the conditions related to the load-displacement curve described above, and may be an inorganic filler or an organic filler. In particular, the filler is preferably an inorganic filler, and examples of the filler include silica, hydroxyapatite, titanium oxide, calcium carbonate, kaolin, aluminum oxide, and the like. Among these, hydroxyapatite-based fillers are preferable. These fillers may be used alone or in combination of two or more kinds.

[0038] The average particle size of the filler is preferably 100 nm or more, more preferably 200 nm or more, and even more preferably 300 nm or more. The average particle size of the filler is preferably 2000 nm or less, more preferably 1800 nm or less, and even more preferably 1500 nm or less. When the average particle size of the filler is within the above range, the obtained release film 1 easily satisfies the conditions related to the load-displacement curve described above.

[0039] When the substrate 11 contains a filler (when the substrate 11 contains a filler throughout its entirety; excluding the case where the substrate 11 has a first resin layer described below), the content of the filler in the substrate 11 is preferably 0.5% by mass or more, and more preferably 0.6% by mass or more. The content of the filler is preferably 1.5% by mass or less, and more preferably 1.4% by mass or less. When the content of the filler is within the above range, the obtained release film 1 is more likely to satisfy the conditions related to the load-displacement curve described above.

[0040] It is also preferable that the substrate 11 at least comprises a layer (first resin layer) containing a filler, and a layer (second resin layer) laminated on one side of the first resin layer and not containing a filler. By providing the first resin layer and the second resin layer in this way, the release film 1 composed of the substrate 11 is more likely to satisfy the above-mentioned conditions regarding the load-displacement curve. The substrate 11 may each comprise only one layer of the first resin layer and the second resin layer, or may comprise two or more layers. A typical example is a substrate 11 in which the first resin layer, the second resin layer, and the first resin layer are laminated in this order.

[0041] The method for producing the substrate 11 is not particularly limited as long as it satisfies the conditions related to the load-displacement curve described above, and the substrate 11 can be produced by, for example, a general method. For example, the substrate 11 can be obtained by forming the above-mentioned resin into a film shape by melt extrusion molding, calendaring, or the like.

[0042] Furthermore, when manufacturing a substrate 11 containing the above-mentioned filler (substrate 11 not having a second resin layer), the substrate 11 can be obtained by adding the filler to the above-mentioned resin and forming it into a film in the same manner as described above.

[0043] The manufacturing method of the substrate 11 including the first resin layer and the second resin layer is not particularly limited. For example, when the above-mentioned resin is extruded, the filler is supplied to the surface of the resin layer immediately after it is formed into a film, and the filler is unevenly distributed only in the surface layer of the resin layer, thereby obtaining the substrate 11. In this case, the first resin layer is formed as the surface layer in which the filler is present, and the second resin layer is formed as the central layer in which the filler is not present. As another manufacturing method, first, a resin to which a filler is added (resin for the first resin layer) and a resin to which a filler is not added (resin for the second resin layer) are respectively prepared, and then the substrate 11 can be obtained by co-extrusion molding these. In addition, the substrate 11 can be obtained by forming these resins into films individually, and then laminating the obtained layers.

[0044] In order to improve adhesion to the release agent layer 12 and the like provided on the surface of the substrate 11, one or both sides of the substrate 11 may be subjected to a surface treatment such as an oxidation method or a roughening method, or a primer treatment, as desired. Examples of the oxidation method include corona discharge treatment, plasma discharge treatment, chromium oxidation treatment (wet), flame treatment, hot air treatment, ozone treatment, and ultraviolet irradiation treatment, and examples of the roughening method include sandblasting and thermal spraying treatment. These surface treatment methods are appropriately selected depending on the type of substrate 11, but generally, corona discharge treatment is preferably used in terms of effectiveness and operability.

[0045] The breaking stress in the width direction of the substrate 11 (the direction perpendicular to the flow direction during the manufacture of the substrate 11; hereinafter sometimes referred to as the "TD direction") is preferably 200 MPa or more, particularly preferably 220 MPa or more, and more preferably 240 MPa or more. The breaking stress in the width direction of the substrate 11 is preferably 340 MPa or less, particularly preferably 320 MPa or less, and more preferably 320 MPa or less. By having the breaking stress of the substrate 11 within the above range, the strength required in each process is sufficiently maintained, the crystallinity of the resin is increased, and the release film 1 is easily able to achieve a large elastic deformation power. The details of the method for measuring the breaking stress are as described in the examples below.

[0046] The breaking elongation in the width direction (TD) of the substrate 11 is preferably 80% or more, particularly preferably 85% or more, and more preferably 90% or more. The breaking elongation in the width direction of the substrate 11 is preferably 120% or less, particularly preferably 110% or less, and more preferably 105% or less. When the breaking elongation of the substrate 11 is in the above range, the release film 1 is less likely to be plastically deformed, and the release film 1 is less likely to be cut by the cutting blade 4, which improves the cuttability of the ceramic green sheet 2. The details of the method for measuring the breaking elongation are as described in the examples below.

[0047] The thickness of the substrate 11 is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more. The thickness of the substrate 11 is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 38 μm or less. When the thickness of the substrate 11 is within the above range, the obtained release film 1 easily satisfies the conditions related to the load-displacement curve described above.

[0048] 3. Release agent layer The release agent constituting the release agent layer 12 is not particularly limited as long as it satisfies the above-mentioned conditions regarding the load-displacement curve when the release film 1 is formed. For example, a silicone-based release agent, a fluorine-based release agent, an acrylic-based release agent, an alkyd-based release agent, a long-chain alkyl group-based release agent, a thermoplastic resin-based release agent, etc. can be used. Among them, it is preferable to use a silicone-based release agent as the release agent constituting the release agent layer 12. These release agents may be used alone or in combination of two or more.

[0049] The silicone-based release agent may be any of addition reaction type, condensation reaction type, ultraviolet curing type, electron beam curing type, etc. Among these, addition reaction type silicone-based release agents are particularly preferred because they have high reactivity and excellent productivity, as well as excellent effects such as small change in release force over time and no cure shrinkage.

[0050] Examples of the addition reaction type silicone-based release agent include a release agent composition containing a base agent made of a polyorganosiloxane compound containing an alkenyl group and a catalyst that promotes the addition reaction. The release agent composition may further contain a crosslinking agent.

[0051] The main skeleton of the polyorganosiloxane compound constituting the base agent or crosslinking agent is, for example, polydimethylsiloxane or dimethylsiloxane-methylphenylsiloxane copolymer. Examples of the alkenyl group used in the polyorganosiloxane of the base agent include alkenyl groups having 2 to 10 carbon atoms, such as vinyl, allyl, propenyl, and hexenyl. The position of the alkenyl group in the polyorganosiloxane may be the molecular terminal or a side chain. It is preferable that the polyorganosiloxane as the base agent has two or more alkenyl groups per molecule.

[0052] The weight average molecular weight of the polyorganosiloxane as the base agent is preferably 50,000 or more, particularly preferably 100,000 or more, and more preferably 150,000 or more. The weight average molecular weight is preferably 1,000,000 or less, particularly preferably 800,000 or less, and more preferably 600,000 or less. The weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) in terms of standard polystyrene.

[0053] By having the weight-average molecular weight of the polyorganosiloxane in the above range, it is easy to achieve excellent coating properties. In addition, by having the weight-average molecular weight of the polyorganosiloxane of 50,000 or more, it is possible to prevent the coating viscosity of the release agent composition from becoming too low, suppress the occurrence of repelling, and easily obtain a release agent layer 12 with a uniform surface condition. Furthermore, by having the weight-average molecular weight of the polyorganosiloxane of 1,000,000 or less, it is possible to effectively suppress the increase in the coating viscosity of the release agent composition, and it is possible to ensure good solubility in a dilution solvent.

[0054] Specific examples of the polyorganosiloxane used in the crosslinking agent include dimethylhydrogensiloxane-methylhydrogensiloxane copolymer endblocked with dimethylhydrogensiloxane, trimethylsiloxy group endblocked dimethylsiloxane-methylhydrogensiloxane copolymer, trimethylsiloxy group endblocked methylhydrogenpolysiloxane, poly(hydrogensilsesquioxane), and the like.

[0055] The catalyst is not particularly limited as long as it can cure the release agent composition, but specific examples include particulate platinum, particulate platinum adsorbed on a carbon powder carrier, chloroplatinic acid, alcohol-modified chloroplatinic acid, olefin complexes of chloroplatinic acid, platinum metal compounds such as palladium and rhodium, etc. The content of the catalyst is preferably about 1 ppm or more and 1000 ppm or less based on the total amount of components other than the catalyst.

[0056] Furthermore, the addition reaction type silicone-based release agent may contain, if desired, an addition reaction inhibitor, a release regulator, an adhesion improver, etc. Furthermore, as materials constituting the release agent layer 12, in addition to the above release agents, antistatic agents, dyes, pigments and other additives may be used.

[0057] The thickness of the release agent layer 12 is preferably 10 nm or more, more preferably 15 nm or more, and even more preferably 20 nm or more. The thickness of the release agent layer 12 is preferably 1000 nm or less, more preferably 800 nm or less, and even more preferably 500 nm or less. When the thickness of the release agent layer 12 is within the above range, the obtained release film 1 easily satisfies the conditions regarding the load-displacement curve described above.

[0058] 4. Middle tier In the release film 1 according to this embodiment, from the viewpoint of making it easier to satisfy the conditions related to the load-displacement curve described above, an intermediate layer may be provided between the substrate 11 and the release agent layer 12. The material of the intermediate layer is not particularly limited, but examples thereof include ultraviolet-curable resins, melamine resins, epoxy resins, alkyd resins, and urea resins.

[0059] When the release film 1 has an intermediate layer, the thickness of the intermediate layer is preferably 10 μm or more, particularly preferably 15 μm or more, and more preferably 20 μm or more. The thickness of the intermediate layer is preferably 1000 μm or less, particularly preferably 800 μm or less, and more preferably 500 μm or less. When the thickness of the intermediate layer is within the above range, the obtained release film 1 is likely to satisfy the conditions related to the load-displacement curve described above.

[0060] 5. Manufacturing method of release film for ceramic green sheet manufacturing process The release film 1 according to this embodiment can be obtained, for example, by applying a coating liquid containing a release agent composition and, if desired, an organic solvent to one surface of a substrate 11, followed by drying and curing to form a release agent layer 12. Examples of the coating method that can be used include gravure coating, bar coating, spray coating, spin coating, knife coating, roll coating, and die coating.

[0061] The organic solvent is not particularly limited, and various organic solvents can be used, such as hydrocarbon compounds such as toluene, hexane, and heptane, as well as acetone, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, and mixtures thereof.

[0062] The coating film obtained by applying the release agent composition as described above is preferably thermally cured. In this case, the heating temperature is preferably 90° C. or higher and 140° C. or lower, and the heating time is preferably about 10 seconds or higher and 120 seconds or lower. If necessary, the curing of the release agent composition may be accelerated by irradiating it with ultraviolet light.

[0063] When the release film 1 according to this embodiment has an intermediate layer, the intermediate layer can be formed on one side of the substrate 11 using a general method according to the material of the intermediate layer. Then, the release agent layer 12 is formed on the surface of the intermediate layer opposite the substrate 11 by the above-mentioned method, thereby obtaining the release film 1.

[0064] 6. How to use release film for ceramic green sheet manufacturing process The release film 1 according to this embodiment can be used to produce a ceramic green sheet. Specifically, a ceramic slurry containing a ceramic material such as barium titanate or titanium oxide is applied to the release surface of the release agent layer 12, and then the ceramic slurry is dried to obtain a ceramic green sheet. Coating can be performed, for example, by using a slot die coating method or a doctor blade method.

[0065] Examples of the binder component contained in the ceramic slurry include butyral resins, acrylic resins, etc. Examples of the solvent contained in the ceramic slurry include organic solvents, aqueous solvents, etc.

[0066] After forming the ceramic green sheet, the ceramic green sheet can be cut on the release film 1. This cutting can be performed by a general method. After the cutting, the release film 1 is peeled off from the ceramic green sheet.

[0067] The release film 1 according to this embodiment satisfies the conditions related to the load-displacement curve described above, and thus the lift 5 is likely to occur in the cut portion of the ceramic green sheet 2 when the release film 1 is cut. Then, when the release film 1 is peeled off from the ceramic green sheet 2, the lift 5 can be used as the starting point. Therefore, the release film 1 according to this embodiment makes it possible to easily peel off the ceramic green sheet 2.

[0068] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention.

[0069] For example, another layer such as an antistatic layer may be provided on the surface of the substrate 11 opposite to the release agent layer 12, or between the substrate 11 and the release agent layer 12, or the like. EXAMPLES

[0070] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0071] [Preparation of substrate] The following substrates A to G were prepared. Of these, substrates A to F were obtained by forming a film by changing the amount and type of filler added to polyethylene terephthalate. <Base material A> Main material: polyethylene terephthalate, filler: hydroxyapatite, thickness: 31μm, breaking stress (MD): 237MPa, breaking stress (TD): 287MPa, breaking elongation (MD): 152%, breaking elongation (TD): 100% <Base material B> Main material: polyethylene terephthalate, filler: hydroxyapatite, thickness: 31μm, breaking stress (MD): 237MPa, breaking stress (TD): 287MPa, breaking elongation (MD): 152%, breaking elongation (TD): 100% <Base material C> Main material: polyethylene terephthalate, filler: hydroxyapatite, thickness: 31 μm, breaking stress (MD direction): 235 MPa, breaking stress (TD direction): 281 MPa, breaking elongation (MD direction): 145%, breaking elongation (TD direction): 97% <Base material D> Main material: polyethylene terephthalate, filler: silica, thickness: 31 μm, breaking stress (MD direction): 232 MPa, breaking stress (TD direction): 285 MPa, breaking elongation (MD direction): 129%, breaking elongation (TD direction): 84% <Base material E> Main material: polyethylene terephthalate, filler: silica, thickness: 31 μm, breaking stress (MD direction): 239 MPa, breaking stress (TD direction): 282 MPa, breaking elongation (MD direction): 145%, breaking elongation (TD direction): 102% <Base material F> Main material: polyethylene terephthalate, filler: silica, thickness: 31 μm, breaking stress (MD direction): 233 MPa, breaking stress (TD direction): 280 MPa, breaking elongation (MD direction): 140%, breaking elongation (TD direction): 99%

[0072] The breaking stress and breaking elongation were measured by a tensile test using a tensile tester (manufactured by Orientec Co., Ltd., product name "Tensilon") in an environment of 23°C and 50% RH, at a tensile speed of 200 mm / min.

[0073] Example 1 100 parts by mass of polyorganosiloxane (weight average molecular weight: 390,000, vinyl group amount in 1 g of polyorganosiloxane: 0.25 mmol, solid content: 30% by mass) having two or more vinyl groups at the terminal or side chain, and the portion not having a vinyl group being a methyl group, was dissolved in toluene to obtain an addition reaction type polyorganosiloxane solution with a solid content of 1.5% by mass. Next, 2 parts by mass of a platinum catalyst (manufactured by Dow Corning Toray Co., Ltd., product name: SRX-212) was added to and mixed with 100 parts by mass of the addition reaction type polyorganosiloxane solution to obtain a coating solution of a release agent composition with a solid content of 1.5% by mass.

[0074] The obtained coating solution of the release agent composition was uniformly applied by a bar coater to one side of the substrate A obtained in Preparation Example 1. The substrate was then dried by heating at 125°C for 60 seconds to harden the release agent composition, thereby obtaining a release film for use in the production process of ceramic green sheets in which a release agent layer having a thickness of 50 nm was laminated on the substrate.

[0075] [Examples 2 to 3, Comparative Examples 1 to 5] A release film for use in the production process of a ceramic green sheet was obtained in the same manner as in Example 1, except that the type of substrate and the thickness of the release agent layer were changed as shown in Table 1.

[0076] [Test Example 1] (Measurement of elastic displacement, plastic displacement and elastic deformation power using a micro surface hardness tester) Using a micro-surface hardness tester (manufactured by Shimadzu Corporation, product name: Dynamic Ultra-Micro Hardness Tester W201S), an indenter was pressed with a load of 20 mN against the release agent layer side of the release film for the ceramic green sheet manufacturing process produced in the examples and comparative examples, and a load-displacement curve was obtained showing the relationship between the indentation depth displacement and the load.

[0077] FIG. 5 shows a schematic of the load-displacement curve obtained. In this load-displacement curve, the load (F) is plotted on the vertical axis, and the indentation depth displacement (d) is plotted on the horizontal axis. As shown in the figure, when the load is increased from the start when no load is applied until the maximum load is applied, the displacement changes from point P0 to point P1 (the displacement amount at this time is designated as "d1") as shown by solid line A. When the load is then removed, the displacement changes from point P1 to point P2 (the displacement amount at this time is designated as "d2") as shown by solid line B. Note that the intersection point of the perpendicular line (dashed line C) to point P1 and the horizontal axis is designated as point P3.

[0078] In the load-displacement curve, the amount of displacement d1 at the time of maximum load (point P1) was defined as the amount of elastic displacement, and the amount of displacement d2 at the time of unloading (point P2) was defined as the amount of plastic displacement. The elastic deformation power was measured by calculating W from the load-displacement curve as the area surrounded by the solid line A, the solid line B, and the horizontal axis. plast (Work of plastic deformation) and W as the area enclosed by the solid line B, the dashed line C, and the horizontal axis elast (elastic deformation work), and using the following equations (1) and (2), W total The elastic deformation power (ηIT) was derived from the ratio of the elastic deformation work to the total deformation work. The results are shown in Table 1. W total =W plast +Welast (1) ηIT=W elast / W total (2)

[0079] [Test Example 2] (Measurement of arithmetic mean roughness and maximum projection height of release agent layer) A double-sided tape was applied to a glass plate, and the release film obtained in the examples and comparative examples was fixed to the glass plate via the double-sided tape so that the opposite side to the side to be measured was the glass plate side. The arithmetic mean roughness (Ra; nm) and maximum protrusion height (Rp; nm) of the release surface and the back surface of the release film were observed at 50x magnification in PSI mode using an optical interference surface profile observation device (Veeco, product name: WYKO-1100), and were measured based on the surface profile image obtained in the range of 91.2 x 119.8 μm. The results are shown in Table 1.

[0080] [Test Example 3] (Evaluation of slurry coatability) A ceramic slurry was prepared by adding 135 parts by mass of a toluene / ethanol mixed solvent (6 / 4 by mass ratio) to 100 parts by mass of barium titanate powder (BaTiO3; manufactured by Sakai Chemical Industry Co., Ltd., product name: BT-03), 8 parts by mass of polyvinyl butyral (manufactured by Sekisui Chemical Co., Ltd., product name: S-LEC B·KBM-2) as a binder, and 4 parts by mass of dioctyl phthalate (manufactured by Kanto Chemical Co., Ltd., product name: Dioctyl phthalate Grade 1) as a plasticizer, and mixing and dispersing the mixture in a ball mill.

[0081] The above ceramic slurry was applied to the surface of the release agent layer of the release film for the ceramic green sheet manufacturing process obtained in the examples and comparative examples using a die coater, and then dried at 80°C for 1 minute. In this way, a ceramic green sheet with a thickness of 3 μm was formed on the release film, and a release film with a ceramic green sheet was obtained. For this release film with a ceramic green sheet, a fluorescent lamp was lit from the release film side, and all the formed ceramic green sheet surfaces were visually inspected, and the slurry coatability was evaluated according to the following criteria. The results are shown in Table 1. ○…There were no pinholes in the ceramic green sheet ×: Pinholes occurred in the ceramic green sheet

[0082] [Test Example 4] (Measurement of peeling force against ceramic green sheet) The release film with the ceramic green sheet produced by the same procedure as in Test Example 3 was left to stand for 24 hours under an atmosphere of room temperature 23 degrees and humidity 50%. Next, it was cut into a size of 100 mm in the flow direction and 40 mm in the width direction. This was used as a measurement sample. An acrylic adhesive tape (manufactured by Nitto Denko Corporation, product name: 31B tape) with a width of 5 mm was attached to one end of the short side of the ceramic green sheet side of the measurement sample. The release film side of this measurement sample was fixed to a flat plate with double-sided tape, and the flat plate was placed horizontally on a peel tester (manufactured by Shimadzu Corporation, product name: AGS-20NX) so that the measurement sample was on the upper side. Then, the end of the ceramic green sheet on the side where the acrylic adhesive tape was attached was peeled off from the release film, and the end was attached to the jig of the peel tester. In this state, the ceramic green sheet was pulled vertically upward (90° peeling) at a peeling speed of 200 mm / min to peel the release film from the ceramic green sheet, and the force required for peeling (peel force; mN / 40 mm) was measured. The results are shown in Table 1.

[0083] [Test Example 5] (Evaluation of sheet lifting) A sheet lifting test was performed using a texture analyzer (manufactured by Eiko Seiki Co., Ltd., product name: TA.XT.plus) by pressing a Thomson blade from the ceramic green sheet side into a release film with a ceramic green sheet manufactured by the same procedure as in Test Example 3 under the following measurement conditions. A high-speed camera (manufactured by Keyence Corporation, product name: VW-5000) was used to evaluate the ceramic green sheet lifting according to the following evaluation criteria. [Measurement conditions] Blade material: Carbide (FM10K) Blade angle: 42 degrees Blade tip width: 2μm Push-in speed: 0.5mm / s [Evaluation Criteria for Sheet Lifting] ◯: The ceramic green sheet was lifted by 1.0 μm or more at the cut portion when the blade came into contact with the substrate. ×: The lift of the ceramic green sheet at the cut portion when the blade came into contact with the substrate was less than 1.0 μm.

[0084] In addition, the samples after the sheet lifting test were observed through the release film with a digital microscope (Keyence Corporation, product name: VHX-1000) to measure the height of the sheet lifting (height indicated by "h" in Figure 3(b)). The results are shown in Table 1.

[0085] [Table 1]

[0086] As is clear from Table 1, the release films for the ceramic green sheet manufacturing process obtained in the examples caused good lifting when the ceramic green sheet was cut. [Industrial Applicability]

[0087] The release film for use in the ceramic green sheet production process of the present invention is suitable for forming ceramic green sheets. [Explanation of symbols]

[0088] 1...Release film 11...Base material 12...Release agent layer 2…Ceramic green sheet 3…Support stand 4…Cutting blade 5…Float

Claims

1. A release film for a ceramic green sheet manufacturing process, comprising a substrate and a release agent layer provided on one side of the substrate, The substrate is made of a polyester resin and contains a hydroxyapatite filler. In a load-displacement curve measured when a load of 20 mN is applied to the release agent layer side of the release film for the ceramic green sheet production process using a micro surface hardness tester, the elastic deformation power is 45% or more, the elastic displacement amount is 1.90 μm or less, and the plastic displacement amount is 1.12 μm or less. A release film for use in a ceramic green sheet manufacturing process.

2. 2. The release film for a ceramic green sheet manufacturing process according to claim 1, characterized in that the base material comprises at least a first resin layer containing the filler, and a second resin layer laminated on one side of the first resin layer and not containing the filler.

3. 3. The release film for use in a ceramic green sheet manufacturing process according to claim 1, wherein the release agent layer has an arithmetic mean roughness (Ra) of 1 nm or more and 20 nm or less on the surface opposite to the substrate.

4. A release film for use in a ceramic green sheet manufacturing process according to any one of claims 1 to 3, characterized in that the maximum projection height (Rp) of the release agent layer on the surface opposite the substrate is 10 nm or more and 200 nm or less.

5. 5. The release film for use in a ceramic green sheet manufacturing process according to claim 1, wherein the release agent layer has a thickness of 10 nm or more and 1000 nm or less.

6. 6. The release film for use in a ceramic green sheet manufacturing process according to claim 1, wherein the thickness of the substrate is 10 μm or more and 100 μm or less.

Citation Information

Patent Citations

  • Antistatic laminated polyester film for mold release

    JP2009233919A

  • Release film for ceramic green sheet manufacturing process

    JP2012224011A

  • Mold release film and method for producing the same

    JP2013060555A

  • Release film for producing ceramic green sheet

    JP2019073003A

  • Release film for producing ceramic green sheet and method for evaluating the same

    JP2020049803A